Structure, evolution, and roles of MYB transcription factors proteins in secondary metabolite biosynthetic pathways and abiotic stresses responses in plants: a comprehensive review - Ziming Ma; Ziming Ma; Lanjuan Hu; Yu Zhong (Frontiers in Plant Science)
Unlike mobile organisms, plants are sessile and thus more vulnerable to environmental stressors. Among these, abiotic stress represents a major constraint that profoundly affects plant growth and development. To cope with these challenges, plants have evolved sophisticated adaptive mechanisms to enhance their stress resilience. Transcription factors (TFs) play a pivotal role in these adaptive processes, as they are activated by diverse stress signals and subsequently modulate the expression of stress-responsive genes, thereby improving plant survival under adverse conditions. The MYB TF family, one of the largest TF families in plants, participates in regulating various biological processes, including growth and development, phytohormone signaling, secondary metabolism and abiotic stress responses. Numerous studies have demonstrated that MYB TFs, upon activation by environmental stimuli, can bind to cis-acting elements in the promoters of downstream stress-responsive genes or interact with other proteins to fine-tune their expression, ultimately enhancing plant tolerance to abiotic stress. Additionally, MYB TFs are integral components of phytohormone signaling pathways involved in stress adaptation. Although extensive research has been conducted on plant stress responses, the interplay between MYB TFs and phytohormones in mediating abiotic stress tolerance remains underexplored. In this review, we examine the structural features, classification, and functional mechanisms of MYB transcription factors. Furthermore, we summarize current knowledge on the roles of MYB TFs (both hormone-dependent and hormone-independent) in plant responses to various abiotic stresses, including drought, salinity, extreme temperatures, nutrient deficiencies, and heavy metal toxicity. We also discuss their regulatory roles in the biosynthesis of secondary metabolites, such as glucosinolates, flavonoids, terpenoids, lignans, and astragalosides. In conclusion, this review consolidates existing findings and provides a foundation for uncovering novel functions and regulatory mechanisms of the MYB TF family. Future research should prioritize MYB TFs as central regulators of abiotic stress-responsive gene networks, with the potential to improve crop stress tolerance and yield, thereby addressing global food security challenges.